The relation between right and left ventricular functions in pediatric dilated cardiomyopathy assessed by tissue doppler : A study in pediatric dilated cardiomyopathy patients at Cairo University Pediatric Hospital - Osama Nasr Eddeen Abdelfattah; Fatma Alzahraa Mostafa Gomaa; Inas Abdelsattar Saad; Nashwa Mostafa Mohammad (Cairo : Osama Nasr Eddeen Abdelfattah, 2013)
Dilated cardiomyopathy is not purely a disease of the left ventricle. Right ventricular systolic and diastolic functions are imparired almost universally in children with dilated cardiomyopathy . Tissue doppler imaging plays an essential role in evaluation of right and left ventricular functions
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Dilated cardiomyopathy; Right ventricular functions; Tissue doppler echocardiography